Migrant Remittances and Information Flows : Evidence from a Field Experiment - Batista, Catia; Narciso, Gaia (Published by Oxford University Press on behalf of the World Bank, 2019)
Do information flows matter for remittance behavior? We design and implement a randomized control trial to quantitatively assess the role of communication between migrants and their international network on the extent and value of remittance flows. In the experiment, a random sample of 1,500 migrants residing in Ireland was offered the possibility of contacting their networks outside the host country for free over a varying number of months. We find a sizeable positive impact of our intervention on the value of migrant remittances sent. Larger remittance responses are associated with individuals who are employed and earn higher incomes. This evidence is consistent with the idea that the observed increase in remittances is not a consequence of relaxed budget constraints due to subsidized communication costs but rather a likely result of improved information, perhaps due to better migrant control over remittance use, enhanced trust in remittance channels due to experience sharing, or increased remittance recipients’ social pressure on migrants.